2019
DOI: 10.1002/pon.5241
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of patients and their family members when receiving bad news about cancer: A qualitative meta‐synthesis

Abstract: Objective This qualitative meta‐synthesis explored the subjective experiences of patients and their family members when receiving bad news about cancer, with a focus on what was important to them during this process and making future recommendations. Methods A search of five electronic databases yielded 587 different records that resulted in 88 articles assessed against the inclusion/exclusion criteria. With the supplement of four additional records, 29 articles were analysed using thematic synthesis. A qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…[ 21 ] The inclusion of the perspective of adult patient caregivers in the current sample attends to the under-representation of this group in the existing qualitative literature. [ 7 ]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 21 ] The inclusion of the perspective of adult patient caregivers in the current sample attends to the under-representation of this group in the existing qualitative literature. [ 7 ]…”
Section: Methodsmentioning
confidence: 99%
“…As a means to increase the credibility of the findings, and to address the possible influence of the primary author's previous knowledge of the topic (conducting a meta-synthesis [ 7 ] and interviews that were not part of the current study) and background (Clinical Psychology trainee, living outside of the study locality) on the themes identified, the themes and supporting evidence were independently reviewed by co-authors. The co-authors had >10 years’ experience with providing psychological services to oncology patients in the study locality, as well as expertise in qualitative research methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] A qualitative meta-analysis study reported that cancer patients wanted to receive the bad news in an appropriate environment and in accordance with their personal preferences and also to meet their psychological needs. [18] The education level of the majority of these patients was a primary school and below. Along with age and education, socio-cultural factors also determine the demands of the patients concerning learning the diagnosis and treatment information.…”
Section: Introductionmentioning
confidence: 98%